2016
DOI: 10.1159/000445724
|View full text |Cite
|
Sign up to set email alerts
|

Aflibercept as First-Line Therapy in Patients with Treatment-Naïve Neovascular Age-Related Macular Degeneration: Prospective Case Series Analysis in Real-Life Clinical Practice

Abstract: Purpose: To assess the 13-month effectiveness and safety of aflibercept in naïve patients with neovascular age-related macular degeneration (nvAMD) in a real-life clinical setting. Methods: Thirty-two treatment-naïve patients with nvAMD participated in a prospective two-center study. Patients received intravitreal injections of aflibercept (Eylea®), a loading dose of three monthly injections (2 mg/0.05 ml) every 4 weeks for the first 3 months, followed by intravitreal injections every 2 months. Results: At 3 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
2
5
0
1
Order By: Relevance
“…e functional and structural benefits achieved confirm those of the two large pivotal clinical trials [13], as well as those others observational studies in clinical practice [14][15][16][17][18][19][20]. However, visual outcomes were lower than those reported previously [13], which may be explained by sociodemographic and disease-related differences in the populations included [18].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…e functional and structural benefits achieved confirm those of the two large pivotal clinical trials [13], as well as those others observational studies in clinical practice [14][15][16][17][18][19][20]. However, visual outcomes were lower than those reported previously [13], which may be explained by sociodemographic and disease-related differences in the populations included [18].…”
Section: Discussionsupporting
confidence: 74%
“…In this sense, pivotal studies showed that intravitreal aflibercept administered in a fixed bimonthly regimen provided satisfactory improvement in visual acuity (VA) after 52 weeks of treatment [13]. Evidence in the clinical setting indicating that the functional results obtained are more modest than those observed in the pivotal clinical trials [8,10,[14][15][16][17][18][19][20]. Patients included in these studies vary greatly with respect to sociodemographic and disease characteristics because of the differences in the time of diagnosis or in local prescription recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…Four other studies looked at bimonthly dosing in a total of 140 patients and evaluated the efficacy of bimonthly dosing for a period of~1 year. [25][26][27][28] The studies showed that patients on average gained+9 EDTRS letters in all studies combined which was equivalent to the results of the larger RCT. Futhermore, the studies looked at a range of different CNV pathologies including PCV, PED and RAP and showed the efficacy of the drug in all subtypes.…”
Section: Beyond the First Yearsupporting
confidence: 58%
“…Sample size estimation was based on previous nAMD studies on treatment use under real conditions in Spain. 11–18…”
Section: Methodsmentioning
confidence: 99%